Effectiveness of Duloxetine versus Other Therapeutic Modalities in Patients with Diabetic Neuropathic Pain: A Systematic Review and Meta-Analysis - Juan José Valenzuela-Fuenzalida; Michelle López-Chaparro; Marisol Barahona-Vásquez; Javiera Campos-Valdes; Javiera Cordero Gonzalez; Pablo Nova-Baeza; Mathias Orellana-Donoso; Alejandra Suazo-Santibañez; Gustavo Oyanedel-Amaro; Héctor Gutiérrez Espinoza (MDPI AG, 2024)
Objectives: Diabetic peripheral neuropathy (DPN) is a chronic complication of diabetes mellitus (DM) with symptoms like intense pain and impaired quality of life. This condition has no treatment; instead, the pain is managed with various antidepressants, including duloxetine. The aim of this study is to analyze the evidence on the efficacy of duloxetine in the management of DPN. Methods: A systematic search in different databases was conducted using the keywords "diabetic neuropathy", "duloxetine therapy", "neuropathic pain", and "Diabetes Mellitus". Finally, eight studies were included in this meta-analysis. Results: All articles comparing duloxetine at different doses vs. a placebo reported significant differences in favor of duloxetine on pain scales like 24 h Average Pain Severity (standardized mean difference [SMD] = −1.06, confidence interval [CI] = −1.09 to −1.03, and p < 0.00001) and BPI Severity (SMD = −0.70, CI = −0.72 to −0.68, and p < 0.00001), among others. A total of 75% of the meta-analyses of studies comparing duloxetine at different doses showed a tendency in favor of the 120 mg/d dose. There were significant differences in favor of duloxetine when compared to routine care on the Euro Quality of Life (SMD = −0.04, CI = −0.04 to −0.03, and p < 0.00001) and SF-36 Survey (SMD = −5.86, CI = −6.28 to −5.44, and p < 0.00001) scales. There were no significant differences on the visual analog scale (VAS) when comparing duloxetine and gabapentin. Conclusions: Duloxetine appears to be effective in the management of DPN in different pain, symptom improvement, and quality of life scales.